Pengembangan Media Permainan Game Kotak Alphabet Berbasis Android Untuk Meningkatkan Keterampilan Pengenalan Huruf Pada Anak Usia Dini - Jusmadi, Evryeni (Jurnal Pendidikan Indonesia, 2025)
The objectives of this study are to: (1) develop android-based alphabet box game media to improve letter recognition skills in early childhood (2) describe the effectiveness of android-based alphabet box game media to improve letter recognition skills in early childhood. The subjects of this study were 25 children aged 5-6 years from Bina Belia Kindergarten, Jl. Raya Tanjung Agung, Tanjung Agung Village, Ulu Musi District, Empat Lawang Regency, the focus of this research is an android-based alphabet box game media to improve letter recognition skills in early childhood. This research was conducted with a "research and development" approach. The goal of research and development is to discover, develop and validate products, so that research can be sustainable. Research and development is the process of producing new products and testing the effectiveness of those products. Based on the analysis used in this study, the following results were obtained: (1) android-based alphabet box game media to improve letter recognition skills in early childhood is considered a concrete platform and attracts children's attention to improve children's motor skills. (2) An android-based alphabet box game media model to improve letter recognition skills in early childhood was developed as a good type of media as a learning tool to improve the motor skills of children of Bina Belia Kindergarten, Jl. Raya Tanjung Agung, Tanjung Agung Village, Ulu Musi District, Empat Lawang Regency. The improvement of letter recognition skills in children is significant based on the results of the t-test with a significance level of 0.00 less than 5%. The use of android-based alphabet box game media to improve letter recognition skills in early childhood. After using android-based alphabet box game media to improve letter recognition skills in early childhood, children's motor abilities were higher than before using android-based alphabet box game media to improve letter recognition skills in early childhood.